1996
DOI: 10.1046/j.1365-2036.1996.51193000.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and late effects of low‐dose famotidine, ranitidine or placebo on pentagastrin‐stimulated gastric acid secretion in man

Abstract: Low-dose famotidine and ranitidine, intended for over-the-counter use, inhibit stimulated gastric acid secretion profoundly in the third and fourth hours after an oral dose. Modest effects are still detectable up to 9 h after dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The dose available over‐the‐counter in the UK is half that of the prescribed formulation and so the question of whether this dose is effective has arisen. There is evidence that this lower dose raises gastric pH, and can be effective for some hours, although as previously mentioned the onset of action is delayed compared with simple antacids 44–48 . Effectiveness has also been demonstrated in patients with heartburn 49 .…”
Section: Drugs For Dyspepsia/heartburnmentioning
confidence: 81%
“…The dose available over‐the‐counter in the UK is half that of the prescribed formulation and so the question of whether this dose is effective has arisen. There is evidence that this lower dose raises gastric pH, and can be effective for some hours, although as previously mentioned the onset of action is delayed compared with simple antacids 44–48 . Effectiveness has also been demonstrated in patients with heartburn 49 .…”
Section: Drugs For Dyspepsia/heartburnmentioning
confidence: 81%
“…3±5 We have previously used a model of pentagastrin-stimulated gastric acid secretion to compare the effect of ranitidine 75 mg and famotidine 10 mg on gastric acid secretion over a 9-h period. 6 These drugs, at the doses studied, were superior to placebo but there was no signi®cant difference between them. Any models designed for the study of the effect of these drugs on gastric acidity should attempt to simulate normal everyday activity.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Grimley et al . found no significant difference in the efficacy of these drugs in subjects with pentagastrin‐stimulated acid secretion 13 . Food intake thus compromises the antisecretory efficacy of both drugs in over‐the‐counter dosages.…”
Section: Discussionmentioning
confidence: 91%
“…These findings are comparable to other studies which have shown that the antisecretory efficacy of these two drugs is detectable for up to 9 h 7 , . 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation